The relationships between reaction time scores and false start penalties of offensive linemen in the National Football League (NFL) - Bowman, J. K.; Krywaruczenko, D.; De Flon, B. G.; Boone, R. T. (Perceptual and Motor Skills, 2024)
Each year in the United States, many factors are considered in the National Football League`s draft process, including scouting reports, interviews, medical tests, and measures of players` strength, speed, anthropometry, and personality. Recently, an increased emphasis has been placed on players` psychometrically measured cognitive abilities. Historically, offensive linemen have been excluded from NFL research, since they do not have individual performance statistics. In this study, we attempted to fill that research gap by investigating correlates of offensive linemen`s measured vigilance/impulsivity. We obtained archival player data from 85 offensive linemen in the years from 2014-2021 prior to each of these players` NFL draft. We then used false start penalties per game (FSPG) as an index of their vigilance/impulsivity (and general success) on the field, and we related those values to Reaction Time tests through hierarchical multiple regression analyses. After controlling for draft placement, these players` higher accuracy on a Choice Reaction Time task accounted for a statistically significant percentage of the variance associated with their FSPG statistics. We discuss the practical utility for player development of these and other cognitive assessments now used in the NFL.